2020
DOI: 10.1186/s12937-020-00618-9
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation affects favorably the frequency of migraine attacks: a double-blind randomized placebo-controlled clinical trial

Abstract: Background Observational studies have shown a link between zinc deficiency and migraine headaches. We aimed to examine the effect of zinc supplementation on the characteristics of migraine attacks in patients with migraine. Methods This randomized clinical trial was conducted on 80 patients with migraine. Patients were randomly assigned to receive either zinc sulfate (220 mg/d zinc sulfate) or placebo (lactose) for 8 weeks. Anthropometric measures, serum zinc concentrations, and characteristics of migraine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 39 publications
(59 reference statements)
4
9
0
Order By: Relevance
“…Moreover, in the current study, the normal range of baseline serum zinc levels in the intervention and CGs were observed. In agreement with our results, a previous study has shown that supplementation with zinc decreases the frequency and intensity of migraine headaches in patients with normal range of serum zinc levels [ 7 ]. However, the exact mechanism of zinc on migraine headache is not fully understood [ 7 ], but the possible mechanisms could be through the role of different aspect of insulin action in the body from inhibition of the lipolysis in adipose tissues, down to reducing free fatty acid release into the circulation and thus improved lipid profile, inhibition of nuclear factor-κB activity, decreased expression of inflammatory factors such as interleukin-6 and tumor necrosis factor α (TNF-α), and thus decreased serum levels of hs-CRP [ 8 33 ], so it seems that zinc supplementation could be beneficial to management of migraine-related complications by improving CVD risk factors such as lipid profile and hs-CRP in migraineurs.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Moreover, in the current study, the normal range of baseline serum zinc levels in the intervention and CGs were observed. In agreement with our results, a previous study has shown that supplementation with zinc decreases the frequency and intensity of migraine headaches in patients with normal range of serum zinc levels [ 7 ]. However, the exact mechanism of zinc on migraine headache is not fully understood [ 7 ], but the possible mechanisms could be through the role of different aspect of insulin action in the body from inhibition of the lipolysis in adipose tissues, down to reducing free fatty acid release into the circulation and thus improved lipid profile, inhibition of nuclear factor-κB activity, decreased expression of inflammatory factors such as interleukin-6 and tumor necrosis factor α (TNF-α), and thus decreased serum levels of hs-CRP [ 8 33 ], so it seems that zinc supplementation could be beneficial to management of migraine-related complications by improving CVD risk factors such as lipid profile and hs-CRP in migraineurs.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our results, in several trials zinc supplementation in various diseases, have shown no significant difference of serum level of hs-CRP [ 7 38 ]. However, the decreasing effect of zinc supplementation on serum level of hs-CRP was reported in elderly subjects and adults with metabolic syndrome [ 8 39 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations